Pembatalan Perkawinan Karena Adanya Pemalsuan Identitas Dalam Kasus Poligami - Prasetyorini, Theresia Eni; Sudarmanto, Kukuh; Arifin, Zaenal; Manurung, Mangaraja (Journal Juridisch, 2024)
This study aims to understand the effects of marriage cancellation law due to the forgery of identity in the case of polygamy according to the Civil Code and constraints as well as solutions to the cancellation of the marriage. This study uses a normative juridical method with a case study approach and analytical descriptive specifications. This study relies on secondary data derived from primary, secondary, and tertiary legal materials. Data collection methods use literature studies and documentary studies which are then analyzed by qualitative analysis and normative analysis methods. The results of the study are (1) the cancellation of marriage according to the Criminal Code results in legal consequences for the husband to pay compensation and interest for his wife or other parties who are disadvantaged while for children who are born are children outside of marriage. (2) Constraints in the cancellation of marriage due to the existence of identity forgery, namely the objection of one of the parties on the grounds that the existence of children born then the solution is to provide guidance for bride and groom candidates, increase the frequency of socialization and demand compensation. Constraints because the procedure for the request for cancellation to the court tends to be complicated and long, the solution is to make a request for marriage prevention to the official recording officer and the court as well as make peace efforts in the case of marriage cancellation. Constraints of differences in legal provisions to the status of children, the solution is legal renewal through the formulation in the draft of the Special Civil Procedure Code that regulates the cancellation of marriage due to the counterfeiting of the identity of the polygamy case. Penelitian ini bertujuan untuk memahami akibat hukum pembatalan perkawinan karena adanya pemalsuan identitas dalam kasus poligami menurut KUHPerdata dan kendala serta solusi terhadap pembatalan perkawinan tersebut. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan studi kasus dan spesifikasi deskriptif analitis. Penelitian ini bertumpu pada data sekunder yang berasal dari bahan hukum primer, sekunder dan tersier. Metode pengumpulan data menggunakan studi pustaka dan studi dokumenter yang kemudian dianalisis dengan metode analisis kualitatif dan analisis normatif. Hasil penelitian yaitu pembatalan perkawinan menurut KUHPerdata berakibat hukum bagi suami harus membayar ganti kerugian dan bunga bagi istrinya atau pihak lain yang dirugikan sedangkan bagi anak yang dilahirkannya berstatus sebagai anak luar kawin. Kendala dalam pembatalan perkawianan karena adanya pemalsuan identitas yaitu adanya keberatan dari salah satu pihak dengan alasan adanya anak yang dilahirkan maka solusinya yaitu memberikan bimbingan bagi calon pengantin dan keluarga keduanya, meningkatkan frekuensi sosialisasi serta menuntut ganti kerugian. Kendala karena prosedur permohonan pembatalan ke pengadilan yang cenderung rumit dan lama maka solusinya yaitu membuat permohonan pencegahan perkawinan ke petugas pencatat pekawinan dan pengadilan serta melakukan upaya perdamaian dalam perkara gugatan pembatalan perkawinan. Kendala perbedaan ketentuan hukum terhadap status anak maka solusinya yaitu pembaharuan hukum melalui perumusan dalam Rancangan Undang-Undang Hukum Acara Perdata Khusus yang mengatur pembatalan perkawinan karena pemalsuan identitas kasus poligami.